Off-target thiol alkylation by the NADPH oxidase inhibitor 3-benzyl-7-(2-benzoxazolyl)thio-1,2,3-triazolo[4,5-d]pyrimidine (VAS2870) - Sun, Qi-An (2012)
Specific inhibitors of the production of reactive oxygen species (ROS) by the NADPH oxidases (Nox’s) are potentially important therapeutic agents in the wide range of human diseases that are characterized by excessive ROS production. It has been proposed that VAS2870 (3-benzyl-7-(2-benzoxazolyl)thio-1,2,3-triazolo[4,5-d]pyrimidine), identified as an inhibitor of Nox2 by small-molecule screening, may serve as an example of such an agent. Here we show that VAS2870 inhibits ROS production in the sarcoplasmic reticulum (SR) of mammalian skeletal muscle, previously identified with Nox4, and thereby abrogates O(2)-coupled redox regulation of the ryanodine receptor-Ca(2+) channel (RyR1). However, we also find that VAS2870 modifies directly identified cysteine thiols within RyR1. Mass spectrometric analysis of RyR1 exposed in situ to VAS2870 and of VAS2870-treated glutathione indicated that thiol modification is through alkylation by the benzyl-triazolopyrimidine moiety of VAS2870. Thus, VAS2870 exerts significant off-target effects, and thiol alkylation by VAS2870 (and closely related Nox inhibitors) may in fact replicate some of the effects of ROS on cellular thiol redox status. In addition, we show that SR-localized Nox4 is inhibited by other thiol alkylating agents, consistent with a causal role for cysteine modification in the inhibition of ROS production by VAS2870.